2011
DOI: 10.1016/j.nbd.2010.11.013
|View full text |Cite
|
Sign up to set email alerts
|

G-CSF administration to adult mice stimulates the proliferation of microglia but does not modify the outcome of ischemic injury

Abstract: Recent evidence suggests that adult bone marrow stem cells reduce tissue damage and promote repair following CNS ischemic injury. Since granulocyte-colony stimulating factor (G-CSF) mobilizes hematopoietic stem cells to the circulating compartment, here we tested whether administration of this drug modifies the outcome of a permanent occlusion of the middle cerebral artery in adult mice. To elucidate the behavior and fate of bloodborne cells in the ischemic brain, we produced chimeric animals, in which hematop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…We have shothat bone marrow-derived monocytes can infiltrate the retina and differentiate into cells with microglial phenotype. 17,36 Previous studies have also shown that microglia in the CNS 37,38 and the retina 39 can proliferate in situ under various pathologic conditions. The increased number of microglial-like cells in paraquat-treated mice could be attributed to immune cell infiltration and in situ proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…We have shothat bone marrow-derived monocytes can infiltrate the retina and differentiate into cells with microglial phenotype. 17,36 Previous studies have also shown that microglia in the CNS 37,38 and the retina 39 can proliferate in situ under various pathologic conditions. The increased number of microglial-like cells in paraquat-treated mice could be attributed to immune cell infiltration and in situ proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…A possible mechanism for this phenomenon is that G-CSF enhances an inflammatory response after stroke [17,29]. Stroke generally disturbs the integrity of the blood-brain barrier, which permits input of inflammatory cells into brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies to endothelial nitric oxide synthase (eNOS), its phosphorylated form (phospho-eNOS) and PECAM-1(CD31) were applied to evaluate the degree of angiogenesis, while that to Akt, its phosphorylated form (phospho-Akt) and caspase-3 to observe cell survival and apoptosis [14][15][16]. Antibody to Iba1, microglial marker, was treated to evaluate intracerebral inflammation [17].…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Considering these mediators have been suggested to contribute to ischemic brain injury [49,50,51,52], it is possible that these cytokines contribute to whatever cell death was evident at this dose. However, treatment with or secretion of these chemokines promotes the proliferation, migration and activation of more microglial and other cells [53,54,55], which in turn would provide support for the containment and resolution of injury. There is also increasing evidence now to show that chemokines such as MCP-1, MIP-1a, MIP-1b, RANTES, GCSF, GMCSF and MIP-2 are also involved in neuroprotection-regeneration [56,57,58,59,60].…”
Section: Discussionmentioning
confidence: 99%